Efficiency of Crop–Livestock Production Systems Under Conservation Agriculture: Scope for Sustainable System Transformation in Rain-Fed Drylands of Tunisia - Oral Communication - Dhehibi, Boubaker; Souissi, Asma; Fouzai, Ayoub; Frija, Aymen; Abdeladhim, Mohamed Arbi; Rekik, Mourad (International Center for Agricultural Research in the Dry Areas, 2023)
Presentation on “Efficiency of Crop–Livestock Production Systems Under Conservation Agriculture: Scope for Sustainable System Transformation in Rain-Fed Drylands of Tunisia” delivered during the International Symposium LESOR'2022 (Djerba-Tunisia, 23-25 November 2022.